Exocytosis through the Lens - Graczyk, Alicja; Rickman, Colin (Frontiers in Endocrinology, 2013)
Exocytosis, the process in which material is transported from the cell interior to the extracellular space, proceeds through a complex mechanism. Defects in this process are linked to a number of serious illnesses including diabetes, cancer and a range of neuropathologies. In neuroendocrine cells, exocytosis involves the fusion of secretory vesicles, carrying signalling molecules, with the plasma membrane through the coordinated interplay of proteins, lipids and small molecules. This process is highly regulated and occurs in a complex three-dimensional environment within the cell precisely coupled to the stimulus. The study of exocytosis poses significant challenges, involving rapidly changing, nano-scale, protein-protein and protein-lipid interactions, at specialised sites in the cell. Over the last decade our understanding of neuroendocrine exocytosis has been greatly enhanced by developments in fluorescence microscopy. Modern microscopy encompasses a toolbox of advanced techniques, pushing the limits of sensitivity and resolution, to probe different properties of exocytosis. In more recent years, the development of super-resolution microscopy techniques, side-stepping the limits of optical resolution imposed by the physical properties of light, have started to provide an unparalleled view of exocytosis. In this review we will discuss how advances in fluorescence microscopy are shedding light on the spatial and temporal organisation of the exocytotic machinery.